Renal CD81 interacts with sodium potassium 2 chloride cotransporter and sodium chloride cotransporter in rats with lipopolysaccharide‐induced preeclampsia. Issue 4 (24th March 2023) - Wang, Ping; Zhu, Gangyi; Wu, Qiaozhen; Shen, Li; Liu, Dan; Wang, Zhiyin; Wang, Weiwan; Ren, Zhiyun; Jia, Yutao; Liu, Mingda; Xue, Ying; Ji, Daxi; et al.
Abstract: The kidney regulates blood pressure through salt/water reabsorption affected by tubular sodium transporters. Expanding our prior research on placental cluster of differentiation 81 (CD81), this study explores the interaction of renal CD81 with sodium transporters in preeclampsia (PE). Effects of renal CD81 with sodium transporters were determined in lipopolysaccharide (LPS)‐induced PE rats and immortalized mouse renal distal convoluted tubule cells. Urinary exosomal CD81, sodium potassium 2 chloride cotransporter (NKCC2), and sodium chloride cotransporter (NCC) were measured in PE patients. LPS‐PE rats had hypertension from gestational days (GD) 6 to 18 and proteinuria from GD9 to GD18. Urinary CD81 in both groups tented to rise during pregnancy. Renal CD81, not sodium transporters, was higher in LPS‐PE than controls on GD14. On GD18, LPS‐PE rats exhibited higher CD81 in kidneys and urine exosomes, higher renal total and phosphorylated renal NKCC2 and NCC with elevated mRNAs, and lower ubiquitinated NCC than controls. CD81 was co‐immunoprecipitated with NKCC2 or NCC in kidney homogenates and co‐immunostained with NKCC2 or NCC in apical membranes of renal tubules. In plasma membrane fractions, LPS‐PE rats had greater amounts of CD81, NKCC2, and NCC than controls with enhanced co‐immunoprecipitations of CD81 with NKCC2 or NCC. In renal distal convoluted tubule cells, silencing CD81 with siRNA inhibited NCC and prevented LPS‐induced NCC elevation. Further, PE patients had higher CD81 in original urines, urine exosomes and higher NKCC2 and NCC in urine exosomes than controls. Thus, the upregulation of renal CD81 on NKCC2 and NCC may contribute to the sustained hypertension observed in LPS‐PE model. Urine CD81 with NKCC2 and NCC may be used as biomarkers for PE. Abstract : CD81 interacts with NKCC2 and NCC in LPS‐preeclampsia rat kidneys and positively regulates NCC in cultured mouse renal‐distal‐convoluted‐tubule cells. The enhanced recruit of NKCC2 and NCC into renal plasma‐membranes in LPS‐preeclampsia rats links to upregulations of CD81. Those changes may contribute to the sustained‐hypertension observed in LPS‐preeclampsia model. Higher CD81 with NKCC2 and NCC in preeclampsia patients than controls are seen in original urines and urine exosomes, and may be used as noninvasive biomarkers for preeclampsia.